2005
DOI: 10.1590/s0034-72992005000500011
|View full text |Cite
|
Sign up to set email alerts
|

Estudo retrospectivo de dez anos em endoscopia das cavidades nasais de pacientes com hanseníase

Abstract: Leprosy is an infectious condition that has a chronic evolution caused by the Mycobacterium leprae. It very often attacks the nasal cavities mucosa independent of its clinical form, even before skin lesions or lesions to other parts of the body arise, in the presence or not of clinical complaints. Aim: To show the efficiency of nasal endoscopy to identify endonasal mucosa lesions and the importance of the Otorhinolaryngologist in the diagnosis and follow-up of Leprosy patients. Study Design: Clinical history s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…Julio et al 29 found that the male gender and an age of 33-54 years was associated with alterations in the nose. These results are important because few studies have evaluated nasal alterations caused by complications of leprosy according to Martins 30 and Silva et al 31 The lepromatous clinical form was associated with neural alterations in the feet. The high rates of neural alterations that were observed in the borderline and lepromatous clinical forms may be explained by the pattern of disease progression over time.…”
Section: Discussionmentioning
confidence: 99%
“…Julio et al 29 found that the male gender and an age of 33-54 years was associated with alterations in the nose. These results are important because few studies have evaluated nasal alterations caused by complications of leprosy according to Martins 30 and Silva et al 31 The lepromatous clinical form was associated with neural alterations in the feet. The high rates of neural alterations that were observed in the borderline and lepromatous clinical forms may be explained by the pattern of disease progression over time.…”
Section: Discussionmentioning
confidence: 99%
“…A vigilant attitude should be maintained towards physical changes from leprosy infection. Significant physical impairments from leprosy include neural impairment, changes in the prominence of cranial nerves caused by lesions in the oral and nasal cavities, and oromyofacial alterations that damage the voice, the hearing, and the functions of the stomatognathic system 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study performed in 2005, the findings of olfactory alterations were obtained in four different forms of leprosy; however such findings were obtained in patients at an advanced stage or in reaction. Hyposmia was found in 7.5% of patients; cacosmia in 2.3%, and anosmia in 0.6% (16,30,31).…”
Section: S O M E P S Y C H I a T R I C P A T H O L O G I E S O C C U mentioning
confidence: 96%